Agroclimate information services adopted in provincial Farmers' Union 5 year-plan, directly benefitting over 19000 households designing and implementing homegardens - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Climate-informed planning was taken up in HaTinh province Farmers' Union five-year plan, and is now practiced on homegarden interventions, benefitting 19216 households (2019) The online agroadvisory has 4000-5000 viewers every day. This was initiated by CCAFS-activities in the climate-smart village on climate-smart agriculture, and the Agro-Climate Information Services (ACIS) approach (P48, P55).